Eksistensi Bisnis Agroindustri Teh Iroet - Vidya, Dinda Vergy; Trimo, Lucyana (Politeknik Negeri Lampung, 2018)
KSU Putera Mekar is the first cooperative to own a tea processing factory directly managed by smallholder tea farmers and produce dried tea products called Iroet tea. The beginning of Iroet Tea factory, they sell their products to PT Sariwangi AEA (Agricultural Estate Agency) and other small companies such as Agriwangi and Elinkindo, but it does not go long. PT Sariwangi broke his contract with the cooperative so that the cooperative did not have a large customer anymore. Cooperative members are decreasing because the cooperative is unable to absorb wet tea tops from farmers and can not afford to pay farmers with pay-weight system, but the agro-industry business still survives. This makes the cooperative requires the chronological know the main cause of bad business cooperatives and the reasons for cooperatives to survive. The research design used in this research is qualitative with case study technique. The method used in this research is descriptive qualitative. The results showed that the main cause of bad business cooperatives is the loss of large consumers and the absence of bailout funds. The reason for the cooperative still persists to this day because the cooperative management has a good orientation to improve the business of Iroet tea agroindustry, supported by the loyalty of cooperative members. Keywords: agroindustry, cooperatives, loyalty, smallholder tea farmer